The Distribution of Aceh Traditional House Architecture in the Dynamics of Urbanization and Its Preservation Efforts - Dedy Afriadi; Saniman Andi Kafri; Nova Eliza; Al Nora Selian (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2026)
Rumoh Aceh, the traditional house of Aceh, is increasingly threatened by rapid urbanization and the growing dominance of modern concrete-based housing, raising concerns about the preservation of cultural identity and local wisdom. This study aims to analyze changes in residential patterns caused by urbanization, examine the transformation of Rumoh Aceh into hybrid architectural forms, and formulate adaptive preservation strategies. A qualitative approach was employed through in-depth interviews, field observations, and literature analysis to explore the relationship between urbanization and the sustainability of traditional architecture. The findings reveal that urbanization has significantly reduced the presence of traditional Rumoh Aceh while encouraging the emergence of hybrid houses that combine traditional spatial values and symbolic elements with modern materials and construction techniques. Rather than representing a simple decline of traditional architecture, this transformation reflects a process of cultural adaptation and negotiation between heritage preservation and contemporary living requirements. The study further identifies community participation, supportive government regulations, and economic incentives as key factors for sustaining traditional architectural values. It concludes that the long-term preservation of Rumoh Aceh depends on collaborative efforts among communities, policymakers, and cultural stakeholders, supported by strategies that integrate cultural tourism and locally based renovation incentives.